PENGETAHUAN DAN SIKAP SISWA DENGAN PRILAKU PENERAPAN KESEHATAN DAN KESELAMATAN KERJA (K3) DI LABORATORIUM - Sutaip Sutaip; Mutia Nur Azizah (Journal of Midwifery and Health Administration Research, 2023)
Background: SMK Expertise Pharmacy has potential hazards found in pharmaceutical laboratories with the three highest priority hazards, namely inhalation of toxic gases, burning and exposure to heat, and being exposed to acid spills. Work accidents while in the work laboratory can be caused by students' behavior or habits that are influenced by lack of knowledge and attitudes about good K3 in accordance with Standard Operating Procedures (SOP) in the work laboratory. This study aims to determine the relationship between knowledge and attitudes with behavior in the application of K3 in the Work Laboratory of SMK Bhakti Husada. Method: This type of research is descriptive analytic with a cross sectional design. The population of this study was all students of SMK Bhakti Husada numbering 80, with a research sample of 65 respondents using random sampling. The analysis used is univariate analysis and bivariate bivariate analysis with Chi square test. Results Most are aged 20-21 53.7%, female 85.1%, have good knowledge 76.1%, have good attitude 92.5%, have good K3 Application Behavior 83.6%. There is a significant relationship between students' knowledge and attitudes with the Behavior of K3 Application at SMK Bhakti Husada Jatibarang, shown by the results of the chi-square test obtained a value of (p-value) = 0.001 which is smaller than the value of α=0.05 and (p-value) = 0.001 which is smaller than the value of α=0.05. Conclusion:The conclusion in this study is that there is a relationship between students' knowledge and attitudes with K3 Application Behavior at SMK Bhakti Husada Jatibarang. The need for the main supervisor teacher in giving examples of complying with regulations / SOPs in laboratory learning. The existence of a K3 guidebook.